PEMBERDAYAAN WARGA BINAAN LEMBAGA PEMASYARAKATAN (LP) PEREMPUAN KELAS III PANGKALPINANG MELALUI KEGIATAN KEWIRAUSAHAAN “CUSTOM BOUQET HANDICRAFT” - Duwi Agustina; Hamsani Hamsani; Ayu Wulandari; Ineu Sulistiana (Jurnal Abdi Insani, 2022)
Correctional institutions (prisons) or known as prisons are a place of coaching and mentoring for inmates to further improve themselves both mentally and physically so that they can re-engage in society and not commit social deviations again. This service activity aims to provide motivation and entrepreneurship training as an alternative to additional family income. The education program at the Correctional Institution is more focused on coaching and training activities for prisoners. The implementation of this service activity was carried out at the Class III Pangkalpinang Women's Correctional Institution by providing an understanding of entrepreneurship and training in making various forms of bouquet crafts to 30 female inmates. Based on the results of the implementation of the service that entrepreneurship is a mental attitude and soul that is always active, creative, empowered, creative, initiative and humble in business in order to increase income in its business activities. During the training process, the inmates of the Correctional Institution were very enthusiastic and followed in detail the stages in the making of the bouquet. So that in this training the inmates can produce various types of bouquet crafts, such as flower bouquets, money bouquets, snack bouquets, and hijab bouquets. Community Service Activities initiated by the service team from UBB do not end here, the service team is committed to continuing to hold similar activities but with different partners, so that community empowerment can be carried out evenly and sustainably. Based on the service activities that have been carried out, this activity can form/develop community groups that are economically and socially independent, and can improve business management skills for the inmates.